Analisis Faktor Penghantar Upaya Peningkatan Kompetensi Profesional Guru - Shinta Nento; Abdul Haris Abdullah (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
Professional competence is one of the four competencies that must be possessed by teachers. Efforts to increase professional competence as a teacher's performance certainly do not stand alone, but have a conducting factor. This study identified and tested some of these conducting factors. Three factors were tested in this study: education and training, activeness in professional organizations, and writing and publishing scientific papers. The study used a survey approach. The target population is teachers who take part in the Teacher Professional Education (PPG) program in office, as many as 150 people. The sample was obtained by simple random sampling determined at 30% or a number of 60 people. Data collection using a questionnaire, distributed via google forms. Data analysis techniques using computer assistance with software SmartPLS 3.2. The research findings obtained from hypothesis testing explain that: 1) The education and training factor has a significant and positive influence of 23% on efforts to improve teacher professionalism; 2) The active factor in professional organizations has a significant and positive influence of 28.5% on efforts to increase teacher professional competence; 3) The factor of writing and publishing scientific papers has a significant and positive influence of 28.5% on efforts to increase teacher professional competence. Therefore, educational organizations can consider this finding so that they always pay attention to the factors that lead to efforts to increase teacher professional competence.